2007
DOI: 10.1016/j.molcel.2007.05.033
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 Modulates Cell Motility by Altering the Acetylation Level of Cortactin

Abstract: Histone deacetylase 6 (HDAC6) is a tubulin-specific deacetylase that regulates microtubule-dependent cell movement. In this study, we identify the F-actin-binding protein cortactin as a HDAC6 substrate. We demonstrate that HDAC6 binds cortactin and that overexpression of HDAC6 leads to hypoacetylation of cortactin, whereas inhibition of HDAC6 activity leads to cortactin hyperacetylation. HDAC6 alters the ability of cortactin to bind F-actin by modulating a "charge patch" in its repeat region. Introduction of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
712
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 643 publications
(740 citation statements)
references
References 39 publications
24
712
2
2
Order By: Relevance
“…At present, the exact mechanism by which cortactin, actin and dynamin function to promote vesicle release is not yet completely elucidated. However, acetylation of cortactin is known to prevent its association with actin [116]. From these results, we propose that alcohol-induced hyperacetylation leads to decreased interactions between actin and cortactin such that cortactin is no longer recruited to sites of clathrin-vesicle formation, thereby inhibiting dynamin recruitment and subsequent vesicle fission.…”
Section: Ethanol-induced Modifications Of the Clathrin Machinerymentioning
confidence: 89%
“…At present, the exact mechanism by which cortactin, actin and dynamin function to promote vesicle release is not yet completely elucidated. However, acetylation of cortactin is known to prevent its association with actin [116]. From these results, we propose that alcohol-induced hyperacetylation leads to decreased interactions between actin and cortactin such that cortactin is no longer recruited to sites of clathrin-vesicle formation, thereby inhibiting dynamin recruitment and subsequent vesicle fission.…”
Section: Ethanol-induced Modifications Of the Clathrin Machinerymentioning
confidence: 89%
“…In 2007, Zhang and collaborators identified an F-actin binding protein, cortactin, as a new target for acetylation. Cortactin acetylation is regulated through different factors (PCAF, p300, HDAC6, and SIRT1), leading to the reduction of cortactin binding to F-actin and cell mobility [189,190]. Recently, Cortactin acetylation was also shown to affect dendritic spine morphogenesis, promoting the dendritic clustering of PSD95 and Shank1, two post-synaptic proteins, in excitatory hippocampal synapses.…”
Section: Non-histone Protein Acetylation In Synaptic Plasticity and Mmentioning
confidence: 99%
“…Early studies found that HDAC6-mediated a-tubulin deacetylation destabilizes dynamic microtubules [3] and promotes an increase in cell motility [4,5]. In addition to a-tubulin, several cytoplasmic proteins including Hsp90 [6,7], cortactin [8], b-catenin [9], peroxiredoxins I and II [10], and Ku70 [11] are regulated in a HDAC6-mediated deacetylation-dependent manner. Strong ubiquitin binding activity [12,13] further adds to the multifunctionality of HDAC6, enabling the regulation of many important processes including cell migration, cell stress response to the cytotoxic accumulation of protein aggregates, and immune synapse formation [1,2].…”
Section: Introductionmentioning
confidence: 99%